1976
DOI: 10.1128/jb.127.1.505-515.1976
|View full text |Cite
|
Sign up to set email alerts
|

Purification, quaternary structure, composition, and properties of D-ribulose-1,5-bisphosphate carboxylase from Thiobacillus intermedius

Abstract: D-Ribulose-1,5-bisphosphate (RuBP) carboxylase has been purified from glutamate-C02-S203 2-_grown Thiobacillus intermedius by pelleting the enzyme from the high-speed supernatant and by intermediary crystallization followed by sedimentation into a discontinuous 0.2 to 0.8 M sucrose gradient. The enzyme was homogeneous by the criteria of electrophoresis on polyacrylamide gels of several acrylamide concentrations, sedimentation velocity and equilibrium measurements, and electron microscopic observations of negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
16
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
(36 reference statements)
7
16
0
Order By: Relevance
“…From the results of sedimentation velocity experiments a sedimentation coefficient of s~o,w--14,0 S (c ~ 0.2.53 mg protein ml -t) was calculated. This value is considerably lower than the average of about 18 S reported for the high molecular weight RuBPCases from various eukaryotic and bacterial sources [11][12][13].…”
Section: Resultsmentioning
confidence: 56%
“…From the results of sedimentation velocity experiments a sedimentation coefficient of s~o,w--14,0 S (c ~ 0.2.53 mg protein ml -t) was calculated. This value is considerably lower than the average of about 18 S reported for the high molecular weight RuBPCases from various eukaryotic and bacterial sources [11][12][13].…”
Section: Resultsmentioning
confidence: 56%
“…agilis is similar to that of T. novellus, A. eutrophus and P. denitrificans [5,6,8,21 ]. Although the molecular weight of RuBPCase from N. agilis is similar to that from T. intermedius it is distinct from the latter which contains only one type of subunit [7]. The significance of the minor component which was slightly smaller than the large subunit of RuBPCase from N. agilis is not clear.…”
Section: Resultsmentioning
confidence: 87%
“…c The enzyme of T. novellus contains large (L) and small (S) subunits but the relative proportions have not been established [22 ]. genic photosynthetic organisms [2,[5][6][7][8]. Like other large RuBPCases [24], the enzyme ofN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purohit et al (22) reported that Thiobacillus intermedius, a carboxysome-containing species, possessed an octameric 0-type RuBPCase (Mr 462,500, s20o. = 18.1S).…”
mentioning
confidence: 99%